A survey of cell biology - Jeon, Kwang W. (International review of cytology, 2006)
International Review of Cytology presents current advances and comprehensive reviews in cell biology - both plant and animal. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research.